### 2 Answers

Relevance

- Engr. RonaldLv 71 month ago
The mistake was on raw (a)

on raw (a), "x + h" was not substitute on the term 7x on the function y = x^2 + 7x

and the negative sign was not distributed on the expression x^2 + 7x.

on raw (b)

(x + h)^2 should be expand like this: (x + h)(x + h) = x^2 + 2hx + h^2

on raw (c)

it should be h + 14x/h

and the rest (d) and (c) are all wrong..

- Log in to reply to the answers

- RobertLv 71 month ago
The problem is using the difference quotient:

[f(x+h) - f(x)] / h

Here f(x) is x² + 7x so

f(x+h) = (x+h)² + 7(x+h)

= x² + 2hx +h² + 7x + 7h

Also, - (f(x)) = - x² - 7x

- Log in to reply to the answers

Still have questions? Get answers by asking now.